ANALYSIS OF RECORDING, CALCULATION AND REPORTING OF VALUE ADDED TAX (VAT) BASED ON E-FAKTUR AT PT. BERKAT REHOBOT MANADO - Lumikis, Riri I. C; Ilat, Ventje (Universitas Sam Ratulangi, 2018)
Value Added Tax (VAT) is a tax imposed at the time the company makes a purchase on Taxable Goods (BKP) / Taxable Services (JKP) charged from the Tax Imposition Basis (DPP). Every purchase of goods to be produced / sold, then the tax imposed on the goods, by Taxable Enterpreneurs (PKP) is a Tax Enter 10% of the sale price before tax as Value Added Tax (VAT) which is the output tax for the tax period concerned. The type of data used in this study is, Qualitative Data is data obtained from data collection techniques through interviews, analysis of focused discussion documents or observations recorded in the report. This research was conducted at PT. Berkat Rehobot. Research conducted on the recording, calculation and reporting of Value Added Tax (VAT) at PT. Berkat Rehobot it can be concluded that this company has done accounting of Value Added Tax (VAT) in accordance with Law Number 42 Year 2009. As for the calculation and reporting using e-Faktur application so that the lack of errors that occur. If there is a lack of delays or correction in reporting due to delays in the delivery of existing Input Tax Invoice. However, the overall calculation and reporting has been in accordance with the Director General of Tax Regulation No. PER-16 / PJ / 2014.Keywords: VAT Recording, Counting and Reporting